Synthesis and Characterization of New Copolymers Containing Subs.-1,3,4-Oxadiazole Ring - Raghad Hamed Ismail (Journal of Global Pharma Technology, 2016)
New copolymers were prepared from monomer (5-vinyl-1H-tetrazole),which prepared from reacted acrylonitrile with sodium azide in presence zncl2 and another monomer was Methyl acrylate. comonomers were polymerization using[BPO]with heating to(80-90)c◦.The second step was prepared copoly acid hydrazide,Then reacted with different aromatic carboxylic acid in presence(pocl3)to optain subs.1,3,4-oxadiazole ring pendant on copoly(5-vinyl-1H-tetrazole-MA) .The prepared copolymers were characterized by FT-IR, and copolymers some of them 1H-NMR, and T.G.Keywords: acrylonitrile, Sodium azide, Copolymerization, Acid hydrazide, 1,3,4-Oxadiazole.